Genetic And Environmental Factors In Cellular Disease Progression: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Cellular disease progression is influenced by intricate interactions between genetic susceptibility and environmental exposures. This systematic review synthesized evidence from ten cohort studies examining the contribution of genetic variation, environmental risk factors, and their interplay across major diseases.Methods: Following PRISMA 2020 guidelines, prospective and nested case-control studies published between 2018 and 2025 were systematically analyzed. Eligible studies integrated genomic variables—such as polygenic risk scores, subtype diversity, or genetic polymorphisms—with environmental and lifestyle factors influencing cellular or molecular disease outcomes.Results: Evidence revealed strong gene–environment interdependence across disease categories. Genetic susceptibility modulated disease risk in HIV-1 (Pang et al., 2024), diabetes nephropathy (Wang et al., 2025), Parkinson’s disease (Hu et al., 2025), and cardiovascular mortality (Fujii et al., 2024). Environmental exposures such as diet, smoking, and microbial composition significantly modified these genetic effects. Predictive models in low-birth-weight and systemic lupus erythematosus (Mizuno et al., 2023; Cui et al., 2023) demonstrated improved accuracy when integrating genetic and environmental parameters.Conclusions: The review highlights the essential role of integrating genomic and exposomic data to understand cellular disease trajectories. The findings reinforce the need for precision prevention frameworks that account for both heritable and modifiable determinants of disease.